Social Security Guide : The White Paper and the Beveridge Report Compared - Great Britain. Office of the Minister of Reconstruction. Social insurance ; Great Britain. Inter-departmental Committee on Social Insurance and Allied Services. Social insurance and allied services ; Beveridge, William Henry Beveridge, Baron, 1879-1963; Clarke, Joan Simeon (London : The Social Security League)
1944-10-01 1944 1940s 20 pages other case by right of need. In the past those who had assistance were thought to have inferior status to those who were receiving benefit. In the future this need not be so. Everything depends on the administration of assistance. There is room here for a further Government pronouncement. 3. HOW MUCH MONEY? — The Government have followed the Beveridge figures almost all the way through the White Paper. But there is a curious omission. Sir William Beveridge tells us why he takes these figures. The Government give no reason at all. The significance is this: Beveridge worked these figures out with a high-powered Committee which included Mr. Seebohm Rowntree and Professor A. L. Bowley, two men who have published more than any others living on the needs and expenditures of British households. This Committee calculated, on the basis of all available information, the exact sums needed to keep average men, women, and children fit, and to keep them adequately clothed and equipped. To this sum Sir William added a margin of 1/6 for single persons and 2/- for a couple. This was in case shopping could not always be done in the most favourable market or without the housewife making a mistake. These figures were, of course, based on nutritional knowledge, and on the average standard of living of working class families at the time the Beveridge Committee was at work. In the future this knowledge may be out of date and new standards may develop. Food which seems sufficient now, may, later turn out to be below scientific estimates, just as the B.M.A. minimum diet of 1933 is already thought to be too low. Once this principle of scientific calculation is admitted, as Beveridge admitted it in his Report, there is obvious need for benefit rates to be recalculated from time to time so that they keep pace with current standards of basic health and nutritional standards. This is the Subsistence Principle. The Government do not admit it. They say nothing about relating benefit to basic needs, and make no provision for the periodic review of rates by scientific experts. Ten shillings to-day buys less than it did in 1925. Old Age Pensioners know this well. Their pension was fixed at 10/- in 1925 and has not since been changed. That is why about one-third of all old age pensioners to-day have to have their pensions supplemented on a personal means test principle. In the same way any benefit sum which is fixed to-day may be too little if the cost-of-living rises appreciably. Sir William Beveridge recognised this. He fixed his rates in the expectation that after the war the cost-of-living will be 25 per cent. higher than it was in 1938. He made it clear in the Report that if prices rise higher than this his figures would need reconsideration:— "These provisional figures allow for a rise of 25 per cent. or a little more in the cost of all necessaries including rent, and including also the margin ... If rents can be kept at their pre-war level, the provisional rates are sufficient for a rise of about 33 per cent. on the other necessaries, including the margin. If, in spite of a rise of materially more than 25 per cent. over all necessaries including rent, the provisional rate ..... for a man 6 15X/2/453/3